2020
DOI: 10.5500/wjt.v10.i10.277
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic: Building organisational flexibility to scale transplant programs

Abstract: The prevailing coronavirus disease 2019 pandemic has challenged our lives in an unprecedented manner. The pandemic has had a significant impact on transplantation worldwide. The logistics of travel restrictions, stretching of available resources, unclear risk of infection in immunosuppressed transplant recipients, and evolving guidelines on testing and transplantation are some of the factors that have unfavourably influenced transplant activity. We must begin to build organisational flexibility in order to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…A study comparing COVID-19 patients waitlisted for kidney transplant with those post kidney transplant found that waitlist status was independently associated with mortality [25]. Efforts to build organizational flexibility at transplant centres and to encourage dialogue between providers have helped the transplant community to continue to provide its live-saving services to patients [26,27].…”
Section: Risk Factors and Outcomesmentioning
confidence: 99%
“…A study comparing COVID-19 patients waitlisted for kidney transplant with those post kidney transplant found that waitlist status was independently associated with mortality [25]. Efforts to build organizational flexibility at transplant centres and to encourage dialogue between providers have helped the transplant community to continue to provide its live-saving services to patients [26,27].…”
Section: Risk Factors and Outcomesmentioning
confidence: 99%